Optimal Interval of Pulse and Breathing Signal Formation - Lukočius, R.; Virbalis, J.A.; Vegys, A. (Elektronika ir Elektrotechnika, 2009)
The human pulse or breathing frequency monitoring is topical for workers who work alone. The suitably accurate measurements must be performed when the level of different parasite signals is significant. There again the sudden variation of parameters or surpassing of admissible limits must be fixed without lag. It is obtained the optimal by noise suppression and quick-acting transfer function of input signal filter based on the optimal filtering theory for discrete systems. This transfer function is realized in processor of microcontroller: the algorithm of signal processing is varied dependently on ratio of input signal variation and noise level - in static regime input signal is integrating, in dynamical regime input signal is transferred to output with minimal delay. Ill. 4, bibl. 3 (in English; summaries in English, Russian and Lithuanian).